Deficient habituation to repeated rectal distensions in irritable bowel syndrome patients with visceral hypersensitivity. Issue 5 (17th March 2015) - Lowén, M. B. O.; Mayer, E.; Tillisch, K.; Labus, J.; Naliboff, B.; Lundberg, P.; Thorell, L.‐H.; Ström, M.; Engström, M.; Walter, S.
Abstract: Background: Irritable bowel syndrome (IBS) patients show evidence of altered central processing of visceral signals. One of the proposed alterations in sensory processing is an altered engagement of endogenous pain modulation mechanisms. The aim was to test the hypothesis that IBS patients with (IBS‐S) and without visceral hypersensitivity (IBS‐N) differ in their ability to engage endogenous pain modulation mechanism during habituation to repeated visceral stimuli. Methods: Brain blood oxygen level dependent (BOLD) response was measured during repeated rectal distension and its anticipation in 33 IBS patients with and without visceral hypersensitivity and 18 healthy controls (HCs). BOLD response to early and late phase of the distension series was compared within and between groups. Key Results: While BOLD response was similar during the early phase of the experiment, IBS‐S showed greater BOLD response than IBS‐N and HCs during the late phase of the distension series. IBS‐S showed increasing BOLD response both to the anticipation and delivery of low intensity rectal distensions in brain regions including insula, anterior and mid cingulate cortex. IBS‐N showed decreasing BOLD response to repeated rectal distensions in brain regions including insula, prefrontal cortex and amygdala. Conclusions & Inferences: These findings are consistent with compromised ability of IBS‐S to respond to repeated delivery of rectal stimuli, both in terms of sensitization of sensory pathways and habituation of emotional arousal. The fact that both IBS subgroups met Rome criteria, and did not differ in terms of reported symptom severity demonstrates that similar symptom patterns can result from different underlying neurobiological mechanisms. Abstract : Brain blood oxygen level dependent (BOLD) response was measured during repeated rectal distension and its anticipation in IBS patients with and without visceral hypersensitivity. BOLD response to early and late phase of the distension series was measured. Our findings are consistent with a compromised ability of IBS subjects with visceral hypersensitivity to respond to repeated delivery of an aversive rectal stimulus, both in terms sensitization of sensory pathways and habituation to emotional arousal. The fact that both IBS subgroups did not differ in terms of reported symptom severity or duration demonstrates that similar symptom patterns can result from different underlying neurobiological mechanisms.